2016
DOI: 10.1371/journal.pgen.1006118
|View full text |Cite|
|
Sign up to set email alerts
|

OVATE Family Protein 8 Positively Mediates Brassinosteroid Signaling through Interacting with the GSK3-like Kinase in Rice

Abstract: OVATE gene was first identified as a key regulator of fruit shape in tomato. OVATE family proteins (OFPs) are characterized as plant-specific transcription factors and conserved in Arabidopsis, tomato, and rice. Roles of OFPs involved in plant development and growth are largely unknown. Brassinosteroids (BRs) are a class of steroid hormones involved in diverse biological functions. OsGKS2 plays a critical role in BR signaling by phosphorylating downstream components such as OsBZR1 and DLT. Here we report in ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
76
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(79 citation statements)
references
References 37 publications
(62 reference statements)
3
76
0
Order By: Relevance
“…The OsGSK1 protein may control the abiotic stress tolerance through suppression of stress responsive genes [42]. However, in the BR signaling pathway the major role of the OsGSK2 kinase is phosphorylation and inhibition of activity of the following transcription factors (described below): OsBZR1, OsLIC, OsDLT, OsRLA1/SMOS1, OsOFP1, and OsOFP8 ( Figure 1) which are crucial for the regulation of the BR-dependent gene expression [24,37,38,48,49,82,83]. In rice (and Arabidopsis) the GSK proteins regulate in the phosphorylation-dependent manner various substrate proteins which represent different signaling and developmental processes.…”
Section: Regulation Of the Br Signaling Relay In Monocotsmentioning
confidence: 99%
“…The OsGSK1 protein may control the abiotic stress tolerance through suppression of stress responsive genes [42]. However, in the BR signaling pathway the major role of the OsGSK2 kinase is phosphorylation and inhibition of activity of the following transcription factors (described below): OsBZR1, OsLIC, OsDLT, OsRLA1/SMOS1, OsOFP1, and OsOFP8 ( Figure 1) which are crucial for the regulation of the BR-dependent gene expression [24,37,38,48,49,82,83]. In rice (and Arabidopsis) the GSK proteins regulate in the phosphorylation-dependent manner various substrate proteins which represent different signaling and developmental processes.…”
Section: Regulation Of the Br Signaling Relay In Monocotsmentioning
confidence: 99%
“…It has also been reported that AtOFP1 and AtOFP4 interact with KNAT7 to enhance KNAT7‐mediated transcriptional repression of target genes, and the interaction is of particular importance in the determination of secondary cell wall formation (Li et al ., ). In addition to interaction with TALE proteins, OsOFP8 (LOC_Os01 g64430) has been shown to interact with OsGSK2, a key negative player in the brassinosteroid (BR) response in rice, and acts as a substrate for OsGSK2, suggesting that OsOFP8 is involved in BR signaling (Yang et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Then, the signal is passed along to a key negative regulator, BRASSINOSTEROID-INSENSITIVE 2 (BIN2), which is dephosphorylated by BRI1 SUPPRESSOR 1 (Li et al, 2001;Mora-Garciá et al, 2004;Kim et al, 2011). In rice, the dephosphorylation of GSK3/SHAGGY-like Kinase (OsGSK2, a rice homolog of Arabidopsis BIN2) releases its suppression on BRASSINAZOLE-RESISTANT1 (OsBZR1), LEAF AND TILLER ANGLE INCREASED CONTROLLER (OsLIC), DWARF AND LOW-TILLERING (OsDLT), OVATE Family Protein 8, and REDUCED LEAF ANGLE1 to activate BR response and increase leaf angle (Bai et al, 2007;Wang, L et al, 2008;Tong et al, , 2012Zhang et al, 2012;Yang et al, 2016, Qiao et al, 2017. The kinase activity of OsGSK2 can also be directly inhibited by membrane protein GW5 (quantitative trait locus for grain width and weight on chromosome 5), which is a calmodulin-binding protein (Liu et al, 2017).…”
mentioning
confidence: 99%